Patterns of functional diversity of macroinvertebrates across three aquatic ecosystem types, NE Mediterranean - GJONI, VOJSAVA; GHINIS, STAMATIS; PINNA, MAURIZIO; MAZZOTTA, LUCA; MARINI, GABRIELE; CIOTTI, MARIO; ROSATI, ILARIA; VIGNES, FABIO; ARIMA, SERENA; BASSET, ALBERTO (Mediterranean Marine Science, 2019)
This study is focused on investigating the variation patterns of macroinvertebrate guilds functional structure, in relation to the taxonomic one, across aquatic ecosystem types along the salinity gradient from freshwater to marine and the resulting implications on guild organization and energy flows. Synoptic samplings have been carried out using the leaf-pack technique at 30 sites of the aquatic ecosystems of the Corfu Island (Greece), including freshwater, lagoon, and marine sites. Here, we analyzed the macroinvertebrate guilds of river, lagoon, and marine ecosystems, as: i. taxonomic composition and population abundance ii. trophic guilds composition and relative abundance; and iii. body size spectra and size patterns. The following variation patterns across the three ecosystem types were observed: a. trophic guild composition and body size spectra were more conservative than taxonomic composition within and among ecosystem types, where, trophic guild and size spectra composition were more similar between river and lagoon ecosystem types than with marine ones; b. a dominance on resource exploitation of large species over smaller ones was inferred at all sites; and, c. higher body size-specific density of individuals was consistently observed in lagoon than in freshwater and marine ecosystems. Results extend previous findings suggesting a common hierarchical organization of benthic macroinvertebrate guilds in aquatic ecosystems and showing that lagoon ecosystems have higher energy density transferred to benthic macroinvertebrates than both freshwater and marine ecosystem types.